Levetiracetam Therapeutic Drug Monitoring in a Large Cohort of Korean Epileptic Patients - Changhee Ha; Hyun-Seung Lee; Eun Yeon Joo; Young-Min Shon; Seung Bong Hong; Dae-Won Seo; Soo-Youn Lee (MDPI AG, 2021)
Levetiracetam is a new antiepileptic drug (AED) used for treating and preventing partial or generalized seizures. The usefulness of levetiracetam therapeutic drug monitoring (TDM) is related to inter- or intra-individual pharmacokinetic variability, drug interactions, and patient noncompliance. We aimed to investigate the levetiracetam TDM status in Korean epilepsy patients. Serum trough levetiracetam concentrations were measured using liquid chromatography-tandem mass spectrometry in 710 samples from 550 patients. The median (range) daily and weight-adjusted levetiracetam doses were 1500 (20-5000) mg and 25.5 (3.03-133.0) mg/kg, respectively. Patients on levetiracetam monotherapy constituted only 19.5% of the population, while 30.1% were on co-medication with valproate and 56.0% with enzyme-inducing AEDs (EIAEDs). Observed levetiracetam concentrations were widely distributed, ranging 0.8-95 mg/L, with a median of 17.3 mg/L. Levetiracetam concentrations were therapeutic, supra-therapeutic, and sub-therapeutic in 58.5% (n = 393), 11.6% (n = 78), and 29.9% (n = 201) of samples, respectively. There was a strong correlation between weight-adjusted levetiracetam dosage and concentrations (ρ = 0.6896, p < 0.0001). In this large-scale clinical study, a large inter-individual difference in levetiracetam pharmacokinetics was observed, and levetiracetam concentrations were influenced by EIAEDs. For individual dose adjustments and monitoring compliance, routine levetiracetam TDM is needed in epilepsy patients.